Limitation on the Number of Groundwater Well Pumps in the Coastal Area of Ternate Island - Ramdani Salam; Rahim Achmad; Muhammad Rusli Muin; Nurdin Abdul Rahman (Universitas Khairun, 2024)
The hydrogeological characteristics of small volcanic islands possess unique attributes. Groundwater flow patterns descend radially and converge in coastal aquifers. The uneven distribution of coastal aquifers sometimes leads communities to extract groundwater from specific points. A notable phenomenon observed in the study area is the presence of dug wells with multiple water pumps. If the combined suction capacity of these pumps exceeds the allowed limit, it has the potential to cause the mixing of saltwater with freshwater. This study utilizes geoelectric methods to delineate the groundwater-saltwater interface beneath the surface. The groundwater-saltwater interface can also be calculated using equations. By knowing the well positions with multiple pumps, it is possible to calculate the allowable number of pumps. The calculations yield a limit of up to 31 pumps per dug well, thereby mitigating the risk of saltwater intrusion. Furthermore, data on the dug well positions within the study area are used to create groundwater table contours and flow models, aiding in the analysis of saltwater pollutant dispersion in the event of intrusion.